THE ONTOGENESIS OF SPEECH DEVELOPMENT - T. E. Braudo; M. Yu. Bobylova; M. V. Kazakova (Русский журнал детской неврологии, 2017)
The purpose of this article is to acquaint the specialists, working with children having developmental disorders, with age-related norms for speech development. Many well-known linguists and psychologists studied speech ontogenesis (logogenesis). Speech is a higher mental function, which integrates many functional systems. Speech development in infants during the first months after birth is ensured by the innate hearing and emerging ability to fix the gaze on the face of an adult. Innate emotional reactions are also being developed during this period, turning into nonverbal forms of communication. At about 6 months a baby starts to pronounce some syllables; at 7–9 months – repeats various sounds combinations, pronounced by adults. At 10–11 months a baby begins to react on the words, referred to him/her. The first words usually appear at an age of 1 year; this is the start of the stage of active speech development. At this time it is acceptable, if a child confuses or rearranges sounds, distorts or misses them. By the age of 1.5 years a child begins to understand abstract explanations of adults. Significant vocabulary enlargement occurs between 2 and 3 years; grammatical structures of the language are being formed during this period (a child starts to use phrases and sentences). Preschool age (3–7 y. o.) is characterized by incorrect, but steadily improving pronunciation of sounds and phonemic perception. The vocabulary increases; abstract speech and retelling are being formed. Children over 7 y. o. continue to improve grammar, writing and reading skills. The described stages may not have strict age boundaries, as soon as they are dependent not only on environment, but also on the child’s mental constitution, heredity and character.